Handbook of administrative ethics - Cooper, Terry L., 1938- (New York : Marcel Dekker, 2001)
This handbook follows the discussion of ethics in significant pieces of public administration literature from the late-19th century to the start of the 21st. It offers theoretical perspective, illustrative cases, and empirical research. This edition includes a new chapter on military ethics.
Preface; Contents; Contributors; Introduction; The Emergence of Administrative Ethics as a Field of Study in the United States; Research and Knowledge in Administrative Ethics; Ethics Education in Public Administration and Affairs; Ethics in In-service Training; The Use of Philosophy in Administrative Ethics; Administration and the Ethics of Virtue; The Public Interest; Deontological Dimensions of Administrative Ethics Revisited; A Teleological Approach to Administrative Ethics; A Dream of What We Could Be; Organizational Structure; Governmental Ethics and Organizational Culture.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Civil service ethics -- United States; Government executives -- Professional ethics -- United States; Civil service ethics; Government executives -- Professional ethics; Fonctionnaires -- Déontologie -- États-Unis.; Hauts fonctionnaires -- Déontologie -- États-Unis.; Fonctionnaires -- Déontologie.; Hauts fonctionnaires -- Déontologie.; POLITICAL SCIENCE -- General; Civil service ethics; Government executives -- Professional ethics; United States; Humaniora -- Filosofi